Facing New Challenges: The Role of Teachers as Agents of Change in the 21st Century - Manalu, Dian Evalin; Sulistyawati, Sulistyawati; Wahid, Wahid; Bahari, Yohanes; Warneri, Warneri (International Journal of Multi Discipline Science (IJ-MDS), 2024)
The 21st century is marked by significant changes in the world of education, especially in terms of technological advances, cultural changes, growing educational needs, and social changes. Therefore, teachers must take a more proactive role in shaping the future of education. The purpose of writing this article was to provide an overview for teachers who want to understand their role as agents of change, as well as concrete steps that can be taken in facing educational changes in changing education for a brighter future. The writing methodology used a qualitative research approach that involves literature analysis and an in-depth understanding of issues relevant to the role of teachers as agents of change in the 21st century. The role of teachers as agents of change was approaching change with an open attitude, mastery of educational technology, development of critical thinking skills, increased social and cultural engagement, a differentiated approach, lifelong learning, a role as a model, and the ability to create a responsive learning environment.